KEYWORD MNEMONIC IN BOOSTING THE STUDENTS’ VOCABULARY MEMORIZATION FOR YOUNG LEARNERS LEVEL - Daniar Sofeny; Siti Muamanah (English Education Department, 2021)
The young learners are mostly easy in memorizing the vocabulary of English as a foreign language, but they also very quickly forget them. They need an effective technique to overcome this problem. This study aims to explain the effectiveness of the Keyword Mnemonic Technique in boosting their English vocabulary memorization. The quasi non-equivalent experimental is used as the research method. The subjects of this study are the thirty students of elementary school class five from Lampung Tahalo. The result shows that the significant value of the independent t-test was 0,000>0,05. It means that there is a difference between the experimental class and the control class. The sample t-test shows a significant number of 0,000>0,05. It means that the student's achievement is good after receiving the mnemonic method. It could be concluded that the keyword mnemonic technique can improve or assist the students in memorizing the English vocabulary. The teacher at the beginner level can use this technique as the strategy to boost the students in memorizing the English vocabularies as a foreign language.